2017
DOI: 10.1186/s12891-017-1493-5
|View full text |Cite
|
Sign up to set email alerts
|

Mortality, readmission, and reoperation after hip fracture in nonagenarians

Abstract: BackgroundOsteoporotic hip fractures are associated with high mortality and morbidity in people of advanced age; however, few studies have investigated the complication rates in nonagenarians. In this study, we applied a competing risk analysis to estimate the mortality, readmission, and reoperation rates after surgery for hip fracture among nonagenarians.MethodsA total of 11,184 nonagenarians (aged ≥ 90) who received surgery for hip fracture during the period 1 January 1997 and 31 December 2010 were selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
50
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 54 publications
8
50
8
Order By: Relevance
“…The increased mortality is significant within the first year after the fracture and extends beyond 10 years. The high mortality in patients with hip fractured is associated with many factors such as age, gender, co‐morbidity disease, fracture type, surgery type, the skills of the surgeons, and the medical care systems. The risk of post‐fracture mortality is also significantly higher for persons who have a subsequent fracture and do not take anti‐osteoporosis pharmacologic therapy following the fracture.…”
Section: Introductionmentioning
confidence: 99%
“…The increased mortality is significant within the first year after the fracture and extends beyond 10 years. The high mortality in patients with hip fractured is associated with many factors such as age, gender, co‐morbidity disease, fracture type, surgery type, the skills of the surgeons, and the medical care systems. The risk of post‐fracture mortality is also significantly higher for persons who have a subsequent fracture and do not take anti‐osteoporosis pharmacologic therapy following the fracture.…”
Section: Introductionmentioning
confidence: 99%
“…The total estimated number of hip fracture in Asian countries will increase from 1.12 million in 2018 to 2.56 million in 2050 [28]. Hip fractures are related to increased morbidity and adverse clinical outcomes during hospitalization and discharge are common and costly occurrences [29]. It is logical to perform surgery as early as possible(Best within 48 hours after hip fracture) in order to avoid these complications, especially to reduce the risk of VTE.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies demonstrated that the mortality rates of nonagenarian hip fracture patients would return to an equivalent mortality risk to the average population at five years after injury [9,[12][13][14][15][16]. Furthermore, less than 5% of patients can survive for more than ten years [16]. Consequently, the five-year survival rate can be considered as a reliable parameter to reflect the long-term outcomes of patients in the extremely elderly suffered hip fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no consensus of definition about the long-term survival for hip fracture patients over ninety. There are few articles discussed the five-year survival of the nonagenarians [9,[16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation